2004
DOI: 10.1159/000077999
|View full text |Cite
|
Sign up to set email alerts
|

Low Thymidylate Synthase Expression in the Primary Tumor Predicts Favorable Clinical Outcome in Resected Gastric Cancer Patients Treated with Adjuvant Tegafur

Abstract: Objective: To assess the thymidylate synthase protein (TS) in tumor cells of resected gastric cancer patients treated with adjuvant tegafur (TG), we reviewed the outcome of 94 randomized patients treated either with adjuvant TG plus mitomycin C (MMC) or MMC alone. Methods: TS was determined in 76 out of 94 patients, previously randomized to receive adjuvant TG, 500 mg/m2/day p.o. for 6 months plus four courses of MMC, 10– 20 mg/m2 i.v. every 6 weeks or MMC alone. An immunohistochemical as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…5%; 2, 5-20%, and 3, 1 20%. The multiplication of the intensity and distribution score was graded as negative (1-4) and positive (6)(7)(8)(9).…”
Section: Immunohistochemistry and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…5%; 2, 5-20%, and 3, 1 20%. The multiplication of the intensity and distribution score was graded as negative (1-4) and positive (6)(7)(8)(9).…”
Section: Immunohistochemistry and Evaluationmentioning
confidence: 99%
“…These studies have shown that the lower the TS activity, the greater the response rate to 5-FU-containing chemotherapy. In contrast, low tumor TS expression levels have been reported to be associated with a strong and high rate of response to 5-FU treatment [7] . Since TS is the main enzyme targeted by 5-FU, measurement of TS activity may be necessary to be able to evaluate the efficacy of 5-FU-based chemotherapy.…”
mentioning
confidence: 98%
“…Multiple clinical studies [4,[29][30][31][32][33] suggest that high expression of TS and DPD and low expression of OPRT are closely associated with resistance to fluoropyrimidinebased chemotherapy. In spite of the DPD expression in the current case, the tumor showed a good response.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, TSER variants were evaluated in the liver metastases of patients, and the analysis suggested that TSER*3 homozygotes demonstrated higher overall TS expression and a lower response rate compared to TSER*2 homozygotes (Marsh et al, 2001). There are other similar examples in the literature as well (Grau et al, 2003;Kawabe et al, 2003); however, most of the studies have been small retrospective studies; hence, their applicability in clinical practice is currently limited. Also, different studies have utilized different methods (ranging from real-time PCR to immunohistochemistry) and tissues (tumor versus surrogate peripheral tissues) to quantify TS levels, thus making direct comparisons of the results problematic.…”
Section: Ts Pharmacogenomicsmentioning
confidence: 98%